Work Effectiveness Efforts to Improve Service Quality in Outpatient Labuang Baji Regional General Hospital Makassar - Tri Wahyudi; Andi Baso Walinga Pawelangi (International Journal of Asian Business and Management, 2023)
The purpose of this study was to describe the efficacy of work done to improve service quality at the outpatient department of Labuang Baji Regional General Hospital Makassar.This research uses a qualitative descriptive approach, and the data analysis used is the Interactive Model Data Analysis, which begins with data collection, data reduction, data presentation, and conclusion drawing. The sampling technique used was incidental sampling. The results of the study obtained show that work ability and work results are good, but officers are still found who leave the workspace and are late returning to it. The level of service satisfaction has not been maximized due to inhibiting factors such as officers using cellphones when providing services, officers who are not in place, and queuing machines that experience interference